The mediating role of cognitive flexibility in the relationship between social support and non-suicidal self-injury among adolescents: a multicenter cross-sectional study - Wang, Chenchen; Zheng, Jiaqi; Shen, Guanghui; Chen, Hong; Ye, Xinwu; Li, Cheng-Han; Wu, Bin (Frontiers in Psychology, 2025)
BackgroundNon-suicidal self-injury (NSSI) is a prevalent and concerning behavior among adolescents worldwide, particularly in China. This study aimed to investigate the relationships between social support, cognitive flexibility, and NSSI, and to examine the potential mediating role of cognitive flexibility in the association between social support and NSSI among adolescents.MethodA multicenter cross-sectional study was conducted with 2,109 adolescents (aged 12–18 years, mean age 15.00 ± 1.65 years, 52.3% female) recruited from 14 psychiatric hospitals/outpatient clinics. Participants completed self-report measures of social support and NSSI, along with a cognitive flexibility assessment using the Wisconsin Card Sorting Test. Structural equation modeling was employed to test the hypothesized mediation model.ResultsSocial support was negatively associated with NSSI frequency (β = −0.11, p < 0.001) and positively related to cognitive flexibility (β = 0.09, p < 0.001). The mediation effect of cognitive flexibility was statistically significant [β = −0.01, 95% CI (−0.01, −0.01)] accounting for 8.33% of the total effect of social support on NSSI. Multi-group analysis revealed that the association between social support and cognitive flexibility was stronger in females (β = 0.11, p < 0.001) compared to males (β = 0.02, p > 0.05).ConclusionThis multicenter study provides evidence for the protective roles of social support and cognitive flexibility against NSSI in adolescents. The findings suggest that cognitive flexibility partially mediates the relationship between social support and NSSI, with notable gender differences. These results highlight the importance of enhancing both social support and cognitive flexibility in interventions aimed at reducing NSSI among adolescents.